Biodegradation of aromatic pollutants by metalloenzymes: A structural-functional-environmental perspective - Lin, Ying-Wu (Coordination chemistry reviews, 2021)
[Display omitted] •Biodegradation of environmental pollutants has been favored for decades.•Significant progress has been made in the biodegradation of aromatic pollutants by metalloenzymes.•Both native and artificial metalloenzymes have been applied for biodegradation.•The progress sheds light on the structure-function relationship of metalloenzymes.•The progress provides clues for applications of metalloenzymes in environmental protection. Environmental security is closely related to public health. Aromatic pollutants constitute a class of hazardous environmental chemicals, such as halophenols and polycyclic aromatic hydrocarbons. Biodegradation of environmental pollutants has been favored for decades. As reviewed herein, significant progress has been made in biodegradation of aromatic pollutants by native metalloenzymes, including heme enzymes (peroxidases and cytochrome P450s), non-heme iron-containing enzymes (Rieske dioxygenases), and copper-containing enzymes (catechol oxidase, tyrosinase, and laccase), and artificial metalloenzymes, including engineered myoglobins, designed manganese peroxidase and de novo designed metalloenzymes, such as those in helical bundles and peptide assemblies, as well as synthetic structural and functional models of natural enzymes. These advances shed light on the structure–function relationship of metalloenzymes, providing clues for potential applications in environmental protection. Future directions for making full use of native and artificial metalloenzymes in environmental science are also prospected.